2003
DOI: 10.1590/s1516-14392003000300007
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of alkynes: synthesis and theoretical properties

Abstract: In this paper we present the synthesis and simulation of alkynes derivatives. Semiempirical calculations were carried out for the ground and first excited states, including the spectroscopic properties of the absorption and emission (fluorescence and phosphorescence) spectra by INDO/S-CI and DNdM-INDO/S-CI methods with geometries fully optimized by PM3/CI. The fact that the theoretical spectra are in accord with the experimental absorption spectra gives us a new possible approach on how structure modifications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…A comparison of the calculated peak positions with the experimental measurements for LU-14, LU-22, and LU-38 is presented in Table , while for LU-30, we could not locate any experimental data. Dale, Suzuki, and Rosseto et al reported the measurements of the optical absorption in diphenylacetylene (chemical analog of LU-14), which are in good agreement with each other. In particular, Suzuki classified the absorption in three bands labeled A, B, and C, located at 4.17, 5.22, and 6.30 eV, respectively.…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…A comparison of the calculated peak positions with the experimental measurements for LU-14, LU-22, and LU-38 is presented in Table , while for LU-30, we could not locate any experimental data. Dale, Suzuki, and Rosseto et al reported the measurements of the optical absorption in diphenylacetylene (chemical analog of LU-14), which are in good agreement with each other. In particular, Suzuki classified the absorption in three bands labeled A, B, and C, located at 4.17, 5.22, and 6.30 eV, respectively.…”
Section: Resultsmentioning
confidence: 55%
“…Robertson and Woodward, 29 based upon X-ray measurements, reported identical values of the single and the phenyl ring bond lengths to be 1.40 Å and a triple bond length of 1.19 Å, in the crystalline phase of diphenylacetylene. Rosseto et al 30 reported spectroscopic measurements on diphenylacetylene, along with PM3/CI level optimized geometries for the gas phase. Their optimized values of the single and the phenyl ring bond lengths were in the range 1.389−1.415 Å, while that of the triple bond was 1.195 Å. Chernia et al 31 also performed geometry optimization for diphenylacetylene at the PM3/RHF level and reported 1.195 Å for the triple bond length, while the other ones were in the range 1.390−1.415 Å.…”
Section: T H Imentioning
confidence: 99%
“…Strong absorption peaks are observed at ∼300 nm in the UV spectra of 5-7 due to the electronic transitions of their diarylacetylene chromophores. 12 Upon photoexcitation, 4 emits a blue light (Figure S4), whose λ max is close to that of its precursor 3 (Table 1) and those of its nonfunctionalized poly-(1-phenyl-1-alkyne) parents, 3 indicating that the light emission is from its poly(1-phenyl-1-pentyne) skeleton. The introduction of the phenylethynyl unit does not affect the emission color but enhances the luminescence efficiency.…”
Section: Revised Manuscript Received December 1 2005mentioning
confidence: 77%
“…The aromatic rings of polymer 4 absorb at ∼240 nm (K band) and ∼280 nm (B band), while its polyene backbone absorbs in the wavelengths longer than 300 nm (Figure S4, Supporting Information). Strong absorption peaks are observed at ∼300 nm in the UV spectra of 5 − 7 due to the electronic transitions of their diarylacetylene chromophores . Upon photoexcitation, 4 emits a blue light (Figure S4), whose λ max is close to that of its precursor 3 (Table ) and those of its nonfunctionalized poly(1-phenyl-1-alkyne) parents, indicating that the light emission is from its poly(1-phenyl-1-pentyne) skeleton.…”
mentioning
confidence: 95%